Hubungan Kategori Hipertensi terhadap Gangguan Irama Jantung pada Lansia Penderita Hipertensi di Nagari Koto Baru, Wilayah Kerja Puskesmas Koto Baru, Kabupaten Dharmasraya - Tamara, Sinta Dwi; Putra, Candra Syah; Putri, Dian Eka (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2025)
Hypertension in the elderly often manifests as Isolated Systolic Hypertension, a condition characterized by a surge in systolic pressure while diastolic pressure conversely decreases. According to statistics from the Koto Baru Public Health Center in Dharmasraya Regency in 2025, there were 672 elderly residents diagnosed with this condition. Uncontrolled blood pressure in the elderly carries a high risk of triggering cardiac rhythm disturbances. This study aims to determine the relationship between hypertension categories and cardiac rhythm disturbances among the elderly in Nagari Koto Baru. This research is an analytical observational study with a cross-sectional approach. The study population consisted of 212 elderly individuals, with a purposive sampling technique resulting in a sample of 68 respondents. Bivariate data analysis was conducted using the Chi-Square test. The findings indicated that most of the elderly experienced moderate hypertension, totaling 34 individuals (50%), and 37 elderly participants (54.4%) experienced tachycardia heart rhythms. Based on the Chi-Square statistical test, a significant relationship was found between hypertension categories and heart rhythm in the elderly, with a p-value of 0.000 (< 0.05). There is a significant correlation between the severity of hypertension and the incidence of cardiac rhythm disturbances (tachycardia) in the elderly. Health professionals at the Koto Baru Public Health Center are advised to integrate heart rhythm screenings into the Elderly Integrated Service Post (Posyandu Lansia) program and to enhance education regarding medication adherence to control blood pressure.